Cele polskiej polityki rozwoju regionalnego a obecny stan zróżnicowania przestrzeni - Markowska-Przybyła, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The assumptions and the aims of regional development policy and spatial development policy in Poland in the context of contemporary changes connected with globalization are presented in the article. It describes the current state of diversity of Polish space in inter- and intraregional dimension as well as its change since 1999. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 143-150